2017
DOI: 10.1016/j.ecoenv.2017.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Physiological traits and antioxidant metabolism of leaves of tropical woody species challenged with cement dust

Abstract: Tropical woody species occurring in limestone outcrops are frequently exposed to particulate material from cement factories. The effects of 60-day cement dust exposure on physiological traits and enzymatic antioxidant system of young plant leaves of Guazuma ulmifolia Lam., Myracrodruon urundeuva Allemão and Trichilia hirta L. were investigated. Cement dust (2.5 or 5mgcm) was applied to the leaf surface or soil or both (leaf plus soil) and plants were maintained at greenhouse. Cement dust barely affected the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
1
1
0
1
Order By: Relevance
“…SOD catalyzes the dismutation of superoxide into oxygen and hydrogen peroxide (Tyagi et al, 2019). Consistent with our results, several studies reported that SOD activity increased in response to dust deposition in plants (Erdal & Demirtas, 2010;Siqueira-Silva et al, 2017;Siqueira-Silva et al, 2016). POD, another antioxidant enzyme, is broadly distributed among plant tissues and plays a significant role in various growth, development, and senescence processes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…SOD catalyzes the dismutation of superoxide into oxygen and hydrogen peroxide (Tyagi et al, 2019). Consistent with our results, several studies reported that SOD activity increased in response to dust deposition in plants (Erdal & Demirtas, 2010;Siqueira-Silva et al, 2017;Siqueira-Silva et al, 2016). POD, another antioxidant enzyme, is broadly distributed among plant tissues and plays a significant role in various growth, development, and senescence processes.…”
Section: Discussionsupporting
confidence: 89%
“…Investigations on dust have mainly focused on the impacts of the different kinds of dust on morpho-physiological changes in plants (Drack & Vázquez, 2018;Hatami et al, 2018;Siqueira-Silva et al, 2017;Siqueira-Silva et al, 2016). Stone crusher dust led to a decrease in grain yield of rice (Oryza sativa.…”
Section: Introductionmentioning
confidence: 99%
“…A espécie possui capacidade de se regenerar naturalmente em solos degradados por processos erosivos e de baixa qualidade (Venturoli, Fagg, & Felifili, 2011;Volpato & Martins, 2013;Bertonha et al, 2016), com alta eficiência no uso do nitrogênio (Silva et al, 2018a), potencial de fitoextração de cobre do solo (Asensio et al, 2018;Asensio et al, 2019) Research, Society and Development, v. 9, n. 11, e2329118851, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.8851 e tolerante ao arsênio (Gomes, Soares, & Garcia, 2014). Apresenta também tolerância à presença de zinco, embora sua germinação diminua em altas dosagens (Gomes et al, 2013a;Gomes et al, 2013b) e resistência à poeira de cimento, mesmo nos primeiros estágios de desenvolvimento (Siqueira-Silva et al, 2016;Siqueira-Silva et al, 2017). Todas essas características qualificam a espécie para integrar projetos de recuperação de áreas degradadas (Ferreira et al, 2015) inclusive em solos contaminados.…”
Section: Biologia Vegetal E Ecologiaunclassified